2020
DOI: 10.2147/prbm.s267066
|View full text |Cite
|
Sign up to set email alerts
|

<p>Intensity of Physical Activity and Depressive Symptoms in College Students: Fitness Improvement Tactics in Youth (FITYou) Project</p>

Abstract: To investigate whether the physical activity at different intensities is correlated with depressive symptoms in college students. Patient and Methods: This cross-sectional study was a part of the Fitness Improvement Tactics in Youth Project, which was conducted in 2017. A total of 2,820 college freshmen aged 15-24 years were included in this study, of whom 699 (24.8%) were males and 2,121 (75.2%) were females. Depressive symptoms were measured using the Self-rating Depression Scale. Physical activity was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
4
15
0
1
Order By: Relevance
“…In terms of the PA-depression relationship among this sample of Finns, although the achievement of both the MPA and VPA guidelines were negatively associated with depressive symptoms, the relationships were not statistically significant. Such findings support other research among college freshmen aged 15-24 years, where there were no associations between MPA and VPA and depressive symptoms (34). Nevertheless, our findings of the lack of significant association between MPA and VPA and depressive symptoms contrast with some studies, where students who reported regular exercise had significantly fewer depressive symptoms (4).…”
Section: Variablesupporting
confidence: 82%
“…In terms of the PA-depression relationship among this sample of Finns, although the achievement of both the MPA and VPA guidelines were negatively associated with depressive symptoms, the relationships were not statistically significant. Such findings support other research among college freshmen aged 15-24 years, where there were no associations between MPA and VPA and depressive symptoms (34). Nevertheless, our findings of the lack of significant association between MPA and VPA and depressive symptoms contrast with some studies, where students who reported regular exercise had significantly fewer depressive symptoms (4).…”
Section: Variablesupporting
confidence: 82%
“…The present study aims to examine the mediating role of orthorexia on the relationships between PA and fear of COVID-19. Previous research found that PA is negatively associated with anxiety and depression as well as negative emotions in university students during the COVID-19 pandemic [6,24,86,87]. The physically inactive group had higher scores of anxiety and depression than the physically active group [24].…”
Section: The Current Studymentioning
confidence: 84%
“…Moreover, insufficient physical activity was a predictor of high anxiety among university students from Poland and Ukraine during the COVID-19 pandemic [6]. The total physical activity level and low-intensity physical activity were inversely associated with depressive symptoms in Chinese college students [86]. A longitudinal study of college students in China indicates that physical activity directly alleviated general negative emotions [87].…”
Section: The Current Studymentioning
confidence: 99%
“…A survey of the impact of health protocols among adolescents in Poland showed that university students experienced high levels of stress and anxiety during the pandemic [2]. Teenagers in the United States who are synonymous with various kinds of activities experience activity restrictions.…”
Section: Introductionmentioning
confidence: 99%